AN ANALYSIS OF ‘A MILLION DREAMS’ SONG : FIGURATIVE LANGUAGES AND MORAL INTERPRETATIONS - Eka Rahmani (STBA Pontianak, 2020)
The qualitative study aims at presenting the results of figurative languages and moral interpretations of A Million Dreams songs. From the analysis, it was indicated that there were eleven types of fig-urative languages and two moral values interpreted from the song. The details of figurative language analysis are 13 imageries (20,6%), 4 personifications (6,3%), 2 paradoxes (3,7%), 14 symbols (22,22%), 6 idioms (9,52%), 9 hyperboles (14,28%), 8 repetitions (12,69%), 1 simile (1,58%), 1 met-aphor (1,58%), 1 assonance (1,58%), and 6 consonances (9,52%). Meanwhile, the moral values were about (1) it was important for young people to have visions for a better future lives; and (2) having companions who could be a place for sharing was valuable. In short, as being comprehended that figurative languages and moral values are two educative elements in songs, the researcher expected that the results of this study would bring significances to the target readers.